2019
DOI: 10.1108/ara-09-2018-0179
|View full text |Cite
|
Sign up to set email alerts
|

Country-level governance, accounting standards, and tax avoidance: a cross-country study

Abstract: Purpose The purpose of this paper is to examine the impact of country-level governance and accounting standards on corporate tax avoidance. Design/methodology/approach This paper is an empirical work using a sample of listed companies from 36 countries. Findings This paper finds that firms resident in countries with stronger country-level governance engage in less tax avoidance. Aspects of stronger country-level governance include higher government effectiveness and regulatory quality, and stronger enforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 62 publications
0
21
0
3
Order By: Relevance
“…Indeed, an external audit is an important instrument for shareholders to ensure the transparency and credibility of financial reports (Habbash and Alghamdi, 2017). In this context, Zeng (2019) have found that firms resident in countries with stronger country-level governance engage in less tax avoidance.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, an external audit is an important instrument for shareholders to ensure the transparency and credibility of financial reports (Habbash and Alghamdi, 2017). In this context, Zeng (2019) have found that firms resident in countries with stronger country-level governance engage in less tax avoidance.…”
Section: Introductionmentioning
confidence: 99%
“…This component represents strategic tax planning as tax benefits arising from operations in multiple jurisdictions imply a permanent tax saving (Abdul Wahab & Holland, 2012;Wang et al, 2019). Although permanent differences and statutory tax rates differences generate similar permanent tax benefits, they entail different levels of tax-motivated and earnings-motivated BTD of which the differences are depending on the countries' international tax and accounting policies or standards (Thomsen & Watrin, 2018;Zeng, 2019). Multinational firms secure tax benefits through various methods, including transfer pricing and income shifting Taylor et al, 2015).…”
Section: Components Of Book-tax Differences and Digital Economy Involvementmentioning
confidence: 99%
“…Researchers find the after-effects of accounting standard harmonization as transparency in accounting statements (Bhat et al, 2016), financial market integration (Dhaliwal et al, 2019), audit efficiency and accuracy (Zhang, 2018) and reduced earnings management (Dayanandan et al, 2016). Thus, a great number of studies explain the nuances of implementing common accounting standards at the firm level (Ipino and Parbonetti, 2017;Onali et al, 2017;Bassemir, 2018;Neel, 2017) and country-level (Juhmani, 2017;Mazzi et al, 2019;Zeng, 2019;Guermazi and Halioui, 2020), but do not explain the spread of IFRS across countries over time. Dufour et al (2014) note that a majority of IFRS studies focus on IFRS adoption and ignores IFRS diffusion.…”
Section: Diffusion Of Ifrs 685mentioning
confidence: 99%